(untitled) (Latakia University Journal -Medical Sciences Series, 2022)
Background : Melasma is a cosmetically disfiguring disorder of facial hyperpigmentation . Recalcitrant melasma is resistant to conventional treatment. Platelet rich plasma ( PRP ) may help to reduce the pigmentation of melasma. Objectives : We evaluated the efficacy of PRP in the treatment of recalcitrant melasma using localized intradermal microinjection technique . Patients and methods : Thirty one female adult patients with recalcitrant melasma were enrolled . WOOD ’s light was used to determine the type of melasma . Autologous PRP was delivered into the lesional melasma skin through intradermal microinjections .Over 4 treatment sessions that each took place every 2 weeks . The response to PRP therapy was measured using modified melasma area and severity index (m MASI ) . Results : At the follow up on the third months , m MASI was significantly reduced by mean 34.23% , p value = 0.0001 . The mixed type of melasma achieved higher response to treatment than the dermal type , ( 42.12% versus 21.43% , p value = 0.005) . The third phototype of skin achieved higher response to treatment than the fourth phototype , ( 42.43% versus 22.43% , p value = 0.0001) .The side effects were mild and resolved spontaneously within a few days . PRP was also useful for rejuvenation of melasma skin . Most patients were very satisfied with this treatment. Conclusion : Intradermal PRP microinjection is an useful , new and safe therapeutic option for recalcitrant melasma .